Improving the Human Resource Capacity of Journal Managers through Open Journal Systems (OJS) Training - Semara, I Made Trisna; Saputra, I Putu David Adi; Chandra, I Made Krisna Adi (Institut Pariwisata dan Bisnis Internasional, 2026)
The Vocational Innovation Product Business Implementation Program is proposed to optimize the potential for financial independence (revenue generating) of vocational higher education institutions through the commercialization of academic expertise in the field of scientific publication management. Although the institution has demonstrated its superior capacity in managing Open Journal Systems (OJS), such as successfully accelerating the accreditation ranking of internal journals significantly at the national level, this technical expertise is currently still documented as a cost center for fulfilling the tridharma obligations. The main problem faced is that the capacity of human resources managing these systems has not yet been standardized towards commercial services, and there is not yet a prototype of a paid service system capable of absorbing the high publication demands from researchers outside the institution. As a solution, this program introduces the innovation of forming a